Imaging current-induced switching of antiferromagnetic domains in CuMnAs - Grzybowski, M.J.; Wadley, P.; Edmonds, K.W.; Beardsley, R.; Hills, Victoria Anne; Campion, R.P.; Gallagher, B.L.; Chauhan, Jasbinder S.; Novák, V.; Jungwirth, T.; Maccherozzi, F.; Dhesi, S.S. (American Physical Society, 2017)
The magnetic order in antiferromagnetic materials is hard to control with external magnetic fields. Using X-ray Magnetic Linear Dichroism microscopy, we show that staggered effective fields generated by electrical current can induce modification of the antiferromagnetic domain structure in microdevices fabricated from a tetragonal CuMnAs thin film. A clear correlation between the average domain orientation and the anisotropy of the electrical resistance is demonstrated, with both showing reproducible switching in response to orthogonally applied current pulses. However, the behavior is inhomogeneous at the submicron level, highlighting the complex nature of the switching process in multi-domain antiferromagnetic films.